PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2014-2016) - Oktiawan Setiadi, 11.05.52.0205; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is to analyze managerial influence, institutional ownership, profitability, company growth and company size on the financial system on the BEI for the 2014-2016 period. The population used in this study is a producing company listed on the Indonesia Stock Exchange (BEI) during 2014-2016. The sampling technique uses purposive sampling. The sample used in this study is the company on the Indonesia Stock Exchange (IDX); The company uses the Rupiah currency; Companies have profits and companies that produce complete data with the variables needed in the study. Analysis tools that are multiple linear regression. The results of the analysis can be concluded: Managerial ownership is significant negative towards debt policy. Positive institutional ownership is not significant to debt policy. Profitability has a negative effect on debt policy. Company size has a significant positive effect on debt policy Keywords: managerial, institutional ownership, profitability, company growth, company size and debt policy